Inferior Survival of Hydroxyapatite versus Titanium-coated Cups at 15 Years - Stilling, Maiken (Springer-Verlag, 2009)
Hydroxyapatite (HA) particles have long been suspected to disintegrate from implant surfaces, become entrapped in joint spaces of orthopaedic bearing couples, and start a cascade leading to progressive polyethylene (PE) wear, increased osteolysis, and aseptic loosening. We compared cup revision at 15 years’ followup in a randomized group of patients with 26 cementless THA components with titanium (Ti) versus first-generation HA coating. We also assessed radiographic PE wear and osteolysis to the 12-year followup or end point revision at a minimum of 5 years (mean, 10.9 years; range, 5–12.6 years). Two Ti-coated cups (17%) and eight HA-coated cups (57%) were revised at 15 years’ followup. Femoral head penetration rate was 0.46 mm/year (standard deviation, 0.26) with the HA-coated cups (n = 12) and 0.38 mm/year (standard deviation, 0.14) with the Ti-coated cups (n = 10); we observed a wide variance of linear wear with the HA-coated cups. We also observed a positive association between high wear rate and revision, and between a high volume of osteolysis and revision. Our findings suggest inferior survival of medium-thickness spray-dried HA-coated cups with individual cases of excessive PE wear and premature cup failure. These findings apply to first-generation modular cups and may not apply to other cup designs and new HA-coating technologies. Level of Evidence: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.